Complete genome sequence of Rhizobium leguminosarum bv trifolii strain WSM2304, an effective microsymbiont of the South American clover Trifolium polymorphum. Issue 1 (January 2010) - Reeve, Wayne; O'Hara, Graham; Chain, Patrick; Ardley, Julie; Bräu, Lambert; Nandesena, Kemanthi; Tiwari, Ravi; Malfatti, Stephanie; Kiss, Hajnalka; Lapidus, Alla; Copeland, Alex; Nolan, Matt; et al.
Abstract Rhizobium leguminosarum bvtrifolii is the effective nitrogen fixing microsymbiont of a diverse range of annual and perennialTrifolium (clover) species. Strain WSM2304 is an aerobic, motile, non-spore forming, Gram-negative rod, isolated fromTrifolium polymorphum in Uruguay in 1998. This microsymbiont predominated in the perennial grasslands of Glencoe Research Station, in Uruguay, to competitively nodulate its host, and fix atmospheric nitrogen. Here we describe the basic features of WSM2304, together with the complete genome sequence, and annotation. This is the first completed genome sequence for a nitrogen fixing microsymbiont of a clover species from the American center of origin. We reveal that its genome size is 6, 872, 702 bp encoding 6, 643 protein-coding genes and 62 RNA only encoding genes. This multipartite genome was found to contain 5 distinct replicons; a chromosome of size 4, 537, 948 bp and four circular plasmids of size 1, 266, 105 bp, 501, 946 bp, 308, 747 bp and 257, 956 bp.